Job satisfaction and burnout syndrome in nurses of the Emergency and Critical Care Hospital San Bartolome, 2010 - Broncano Vargas, Yrma Nilda (2019)
Objective: To establish the relationship between job satisfaction and the prevalence of burnout syndrome innurses in the Hospital San Bartolomé Lima Peru. Material and Methods: Quantitative approach, descriptive,prospective, cross-sectional and co-relational study. Population sample: 45 nurses of the Emergency and CriticalCare Services, August 2010. The social and occupational data sheet was used for this research. Also, J.L. Melia’sJob Satisfaction Questionnaire S21/26 and the Assessment Questionnaire burnout syndrome bound to work(CESQT) by Pedro Gil-Monte. The data were processed in SPSS version 18, statistical test for related: chi square.Results: There is high Burnout in moderately satisfied nurses (50%); without a statistic significant association(p = 0.914), rejecting the null hypothesis. The nurses who have low Burnout on the illusion dimension forwork, have greater job satisfaction (75%), existing statistical significant association (p = 0.018 <0.05). Thosewith high and low on Burnout psychological exhaustion are satisfied with work, without statistical association.Those with high burnout indolence dimension are fairly satisfied, without statistical association and those withhigh burnout on the guilt dimension are dissatisfied or moderately satisfied with their work, without a significantstatistical association. Conclusions: There is no statistical significant relationship between job satisfaction andthe burnout prevalence syndrome in nurses, as well as in their psychological exhaustion, indolence and guiltdimensions. There is a statistical meaningful relationship between job satisfaction and the burnout syndrome intheir enthusiasm for the work dimension.